The use of patient reported outcome measures in oncology clinical practice across Australia and New Zealand - Ashika D. Maharaj; Natasha Roberts; Michael Jefford; Jerome Ng; Claudia Rutherford; Bogda Koczwara (SpringerOpen, 2024)
Abstract Background While there is increasing evidence on the benefits of PROMs in cancer care, the extent of routine collection and use of PROMs in clinical cancer practice across Australia and New Zealand (ANZ) is unknown. This study examined the prevalence and characteristics of PROMs use in routine clinical cancer care in ANZ. Methods An online survey was designed and disseminated via professional societies and organisations using a snowball sampling approach to clinical and health administration professionals managing cancer care in ANZ. A poster advertising the study was also circulated on professional social media networks via LinkedIn and Twitter inviting health professionals from ANZ to participate if they were using or intending to use PROMs in clinical cancer practice. Responders opted into the survey via the survey link. Results From 132 survey views, 91(response rate, 69%) respondents from 56 clinical practices across ANZ agreed to participate in the survey, and of these 55 (n = 55/91, 60%) respondents reported collecting PROMs within their clinical practice. The majority of the respondents were from the State of New South Wales in Australia (n = 21/55, 38%), hospital (n = 35/55, 64%), and a public setting (n = 46/55, 83%). PROMs were collected in all cancer types (n = 21/36, 58%), in all stages of the disease (n = 31/36, 86%), in an adult population (n = 33/36, 92%), applied in English (n = 33/36, 92%), and used to facilitate communication with other reasons (27/36, 75%). A geospatial map analysis provided insights into the variation in PROMs uptake between the two countries and in certain jurisdictions within Australia. This study also highlights the limited resources for PROMs implementation, and a lack of systematic priority driven approach. Conclusion PROM use across Australia and New Zealand seems variable and occurring predominantly in larger metropolitan centres with limited standardisation of approach and implementation. A greater focus on equitable adoption of PROMs in diverse cancer care settings is urgently needed.